Neuroprotection of Heme Oxygenase-2 in Mice AfterIntracerebral Hemorrhage. Issue 5 (15th April 2021) - Zhang, Ze; Pang, Yuxin; Wang, Wei; Zhu, Hong; Jin, Sinan; Yu, Zihan; Gu, Yunhe; Wu, He
Abstract: There are few effective preventive or therapeutic strategies to mitigate the effects of catastrophic intracerebral hemorrhage (ICH) in humans. Heme oxygenase is the rate-limiting enzyme in heme metabolism; heme oxygenase-2 (HO-2) is a constitutively expressed heme oxygenase. We explored the involvement of HO-2 in a collagenase-induced mouse model of ICH in C57BL/6 wild-type and HO-2 knockout mice. We assessed oxidative stress injury, blood-brain barrier permeability, neuronal damage, late-stage angiogenesis, and hematoma clearance using immunofluorescence, Western blot, MRI, and special staining methods. Our results show that HO-2 reduces brain injury volume and brain edema, alleviates cytotoxic injury, affects vascular function in the early stage of ICH, and improves hematoma absorbance and angiogenesis in the late stage of ICH in this model. Thus, we found that HO-2 has a protective effect on brain injury after ICH.